Expedited Cross-Training: An Approach to Help Mitigate Nurse Staffing Shortages. Issue 6 (November 2021) - Patel, Sapna; Hartung, Benjamin; Nagra, Roxana; Davignon, Amy; Dayal, Taranvir; Nelson, Maria
Abstract : Cross-training of nurses is an approach used by hospitals to mitigate anticipated nurse staffing shortages. This article provides professional practice nurse educators guidance on how to plan, implement, and evaluate expedited cross-training that integrate the principles of just-in-time training. Sixty-one nurses in a postacute care hospital setting were cross-trained over the course of 8 weeks using a six-step method.